Performance, Physiological Status, and Rumen Fermentation Profiles of Pre- and Post-Weaning Goat Kids Fed Cricket Meal as a Protein Source - Astuti, D. A.; Anggraeny, A.; Khotijah, L.; Suharti, S.; Jayanegara, A. (Tropical Animal Science Journal, 2019)
This study was conducted in two experiments with the objectives: (1) to evaluate nutrient intake, physiological status, and performance of pre-weaning goat kids fed with milk replacer containing cricket meal, and (2) to evaluate nutrient intake, rumen fermentation characteristics, blood profiles, and production performance of post-weaning etawah crossbred goats fed with cricket meal as a substitution of soybean meal. Twelve pre-weaning goat kids (3.78±0.50 kg BW) were divided into 3 treatments (4 replicates per treatment), i.e., kids fed with goat milk (GM), cow milk (CM), and milk replacer containing cricket meal (MR). In the second experiment, 12 post-weaning goats (12-14 kg BW) were fed with 3 dietary treatments, i.e., control ration (CM-0), ration containing 15% cricket meal (CM-15), and ration containing 30% cricket meal (CM-30). Parameters measured during 2 months observations were nutrient intake, physiological status, fermentation profiles, blood profiles, and performance. Both experiments used a completely randomized design. Results showed that there were no significant differences in physiological status parameters in pre-weaning goat kids fed with GM, CM or MR. The performance of kids fed with GM was significantly higher (120 g/d) than those fed with CM and MR treatments (p